Empowering “resilience-building agents”: An analysis of physical education teachers’ instructional intentions for disaster preparation - Gokmenoglu, Tuba; Sonmez, Elif Dasci; Durmus, Ceyda; Karakullukcu, Omur Fatih (International journal of disaster risk reduction, 2025)
Physical education teachers hold unique characteristics, making them prominent figures in disaster education due to their expertise in physical preparedness, coordination, and safety. This study focuses on understanding the psychological and contextual factors that influence PE teachers' intentions to engage in two domains: their personal disaster preparedness behaviors and their instructional intentions to integrate disaster education into their teaching practices in Türkiye. Grounded in Protection Motivation Theory and Paton's social-cognitive framework, the data of 6,195 teachers from twelve provinces were analyzed by descriptive and inferential statistics. Structural equation modeling revealed the interplay between beliefs, critical awareness, perceived severity, trust, empowerment, self-efficacy, positive outcome expectancy, and response cost in shaping both general and teaching intentions for disaster preparedness. While teachers reported moderate levels of disaster preparedness behavior, their intentions to educate students on disaster-related topics were notably stronger. The findings highlight the importance of strengthening institutional support and psychological empowerment to bridge the gap between intention and action. Implications are discussed for policy, teacher education, and school-based disaster education strategies.